Antinociceptive activity of the methanol extracts of leaves of Eugenia fruticosa (Roxb.) and Glycosmis pentaphylla (Retz.) in Swiss albino mice - K. M. Shams-Ud-Doha, Mehnaj Akter, Zobaer Al Mahmud, Apurba Sarker Apu, Md. Amran Howlader (Journal of Applied Pharmaceutical Science)
The present study was designed to evaluate analgesic potential of the methanolic extracts of the leaves of the both Glycosmis pentaphylla (Rutaceae) and Eugenia fruticosa (Myrtaceae). The analgesic activity was evaluated using the acetic acid (0.7% i.p.)-induced writhing inhibition method in swiss albino mice. The methanolic extract of leaves of Glycosmis pentaphylla, at the dose of 200 and 400 mg/kg body weight significantly (p
Keywords: Glycosmis pentaphylla,Eugenia fruticosa, Methanolic extract, Writhing, Acetic acid, Antinociceptive activity.